2020
DOI: 10.1111/eos.12683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bioactive glass air‐abrasion on the wettability and osteoblast proliferation on sandblasted and acid‐etched titanium surfaces

Abstract: The aim of this study was to evaluate the hydrophilicity, surface free energy, and proliferation and viability of human osteoblast‐like MC3T3‐E1 cells on sandblasted and acid‐etched titanium surfaces after air‐abrasion with 45S5 bioactive glass, zinc‐containing bioactive glass, or inert glass. Sandblasted and acid‐etched titanium discs were subjected to air‐abrasion with 45S5 bioactive glass, experimental bioactive glass (Zn4), or inert glass. Water contact angles and surface free energy were evaluated. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…In part, this drop in cell proliferation could have been due to the short time interval between both evaluations (2 days), which technically would have allowed less time for the cells to adapt to the new environment and proliferate; however, toward day 10, when the cells had more time to adapt, the proliferation level increased. This decrease in cell proliferation does not necessarily imply that cells are dying, as they might be reacting to the surface through differentiation rather than proliferation, and increased proliferation might be a reaction to environmental stimuli [ 31 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In part, this drop in cell proliferation could have been due to the short time interval between both evaluations (2 days), which technically would have allowed less time for the cells to adapt to the new environment and proliferate; however, toward day 10, when the cells had more time to adapt, the proliferation level increased. This decrease in cell proliferation does not necessarily imply that cells are dying, as they might be reacting to the surface through differentiation rather than proliferation, and increased proliferation might be a reaction to environmental stimuli [ 31 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous data [27] have shown that some glass particles remain adhered to or embedded inside the pores on the abraded SA surface after BG air‐abrasion. Furthermore, our previous study demonstrated that air‐abrasion of SA discs with 45S5 BG, Zn4 BG, or inert glass results in smoother surface topography than is seen for SA without glass particle air‐abrasion (Figure 7) [31].…”
Section: Discussionmentioning
confidence: 99%
“…*** p < 0.001. Data were extracted from previous publication [31]…”
Section: Discussionmentioning
confidence: 99%
“…SLA : Currently, SLA is the most commonly used strategy for surface modification of implants [ 45 ]. This strategy means that the abrasive medium material is sprayed on the surface of the implant by high-speed air flow to form a depression [ 46 , 47 ]. After that, acid etching is used to form smaller secondary structures and to clean impurities on the implant surface [ 48 ].…”
Section: Local Drug Delivery Systems With Ti-based Implantsmentioning
confidence: 99%